MODERN OPPORTUNITIES FOR AIR SAFETY MANAGEMENT - Kharchenko, Volodymyr; Babeichuk, Dmytro; Pechevysty, Ruslan; Alexeiev, Oleh (Proceedings of National Aviation University (archive), 2020)
The article deals with the management of the basic elements of safety management system (SMS), due to a radical change in industrial relations and the creation of "non-punitive" production environment, and determination of the attitude to the experts in the course of their erroneous actions, as well as the introduction of a system of voluntary notification of personnel about dangerous factors (risk factors), mistakes and incidents. The basis for the creation of reliable functioning of SMS is the formation of modern professional and corporate culture in the airline, enterprise, aviation administration and more. An important part of it is a positive safety culture, which in the aggregate should allow us to reach an acceptable level of safrty flight.